THE GROUP CONCEPT OF BUILDING RASO BATALUN IN THE PERFORMANCE OF TALEMPONG RENJEANG ANAM SALABUHAN - Andar Indra Sastra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The goal of this article is to discuss talempong renjeang anam salabuhan as a cultural artefact, in particular focusing on the group concept of building raso batalun in the performance of talempong renjeang anam salabuhan in Luhak Nan Tigo, Minangkabau. Raso batalun in the performance of talempong is the musical expression created by the talempong player through the rhythmic treatment of the talempong. The expression produced in a talempong performance can be understood to reflect the musical ability of the talempong group in its performance of various types of Guguah talempong. A group is the representation of a social concept in Minangkabau society. Some talempong groups are formed on the basis of common goals and interests without any family connections; other groups are formed through family ties; and others are formed based on genealogical connections. A musical unit is built through musical communication between the talempong players through different rhythmic patterns. This musical communication can be achieved when the players in the group have the same level of perception, ability, and sense of musicality. It is this perception and sense of musicality which are the initial foundations on which a talempong performance is built, in accordance with the musical standard of each group. It is believed that a high musical standard will not be reached if the role of a particular player is taken over by another player from outside the group. The group plays an important role in building a musical unit and a musical standard in order to achieve raso batalun.